Bacteroides congonensis sp. nov., a new bacterial species from the human gut microbiota. (December 2016) - Bilen, Melhem; Cadoret, Frederic; Daoud, Ziad; Fournier, Pierre-Edouard
Abstract: We herein describe the main characteristics of Bacteroides congonensis sp. nov. strain Marseille-P3132 T (CSUR P3132) that was cultivated from a stool specimen of a healthy 35-year-old female pygmy from Congo.